Implications of Matthew 5:23-24 for Conflict Resolution in Educational Settings - Mary Ifechukwude Egwuanikwu (dialektika kontemporer, 2026)
Conflict is certain in relationships that exist among individuals, especially in educational environments with people from diverse backgrounds and values who interact with one another. This paper examined conflict resolution in educational settings from a biblical viewpoint, with particular focus on the principles of reconciliation and forgiveness from Matthew 5:23–24. It made use of a theological technique and incorporated biblical exegesis with models of conflict resolution, which include Restorative Justice (RJ), Social–Emotional Learning (SEL) and Mediation Theories. The exegetical analysis of Matthew 5:23–24 relates three fundamental imperatives—urgency, initiative, and relational priority—which symbolise a model that tackles both spiritual and interpersonal aspects of conflict. Data was obtained from biblical commentaries, published books and articles. The study discovered that applying these principles can modify school culture by encouraging confidence, compassion, and shared respect, ultimately improving learning outcomes. However, while it might be easy for Faith-based schools to discover and express scriptural integration, secular or multi-faith institutions might need to outline the model in a language that is generally acceptable. The paper concluded that reconciliation-centred conflict resolution is not merely biblically authorised but also pedagogically effective, providing a structure for better and more peaceful educational settings. Thus, it is recommended that teachers, administrators, and student leaders in schools should adopt restorative practices, mediation expertise, and Social–Emotional Learning (SEL).